The legal path for priority setting in Chile: a critical analysis to improve health planning and stewardship - Espinoza, Manuel Antonio; Cabieses, Baltica; Goic, Carolina; Andrade, Alejandro (Frontiers in Public Health, 2024)
Health systems have committed their path to universal health coverage using health planning to accomplish their goals of efficiency, equity and sustainability. Chile, a high-income country with a public-private mix health system, has made significant progress through several successive health policies implemented in the last 20 years which have been consistent with this approach. However, in the last 5 years, the national congress has produced several disease-specific laws, which have been mainly promoted by the civil society. These laws indicate the actions the health authority must perform to tackle the needs of the affected population, which ultimately determine the priorities of the health system. We argue that this legal pattern has become an alternative path to priority-setting, as opposed to health planning. We claim this “legal path” is a mechanism used by civil society in a context where the health authority fails to implement a robust and legitimate prioritization process. Although these laws have brought benefits to patients suffering the corresponding conditions, we highlight this approach does not guarantee improvements in equity, efficiency and health system performance. Instead, we advocate for taking back the control of the priority-setting based on health planning, through a new institutionalization of health technology assessment and quality of care.